Gestational Diabetes Mellitus (Diversity Research: Journal of Analysis and Trends, 2023)
Data from a comparative analysis of specific diagnostic symptoms in GDM in pregnant women, for a detailed description of changes in the body of a pregnant woman with GDM, we studied the concentration of homocysteine in the blood for comparison in two study groups - 36 healthy and 68 pregnant women with GDM. According to the analysis of blood in the case histories of patients in groups, anemia was observed in an average of 61.45% of patients.